IHK: Intelligent autonomous agent model and architecture towards multi-agent healthcare knowledge infostructure - Hashmi, Zafar; Adwan, Somaya Maged (2010)
Intelligent autonomous agents is an emerging technology that excels the applications, having complex distributed nature and requiring communication of complex and diverse forms of information, when deployed in multi-agent system setting.As healthcare is a complex domain and distributed in nature, scientist have started to deploy intelligent agents and multi-agent technologies indifferent healthcare information and decision support systems. We argue that efficacy of multi-agent system and performance of multi-agent system architecture in any domain, in particular healthcare domain heavily depends on a single agent architecture and model that mimic human behavior.In this paper we present, Hybrid Intelligent Autonomous Agent (IAA) Model, Hybrid Intelligent Autonomous Agent (IAA) Architecture, and based on these two fundamental building blocks, designing and development of an Intelligent Multi-agent Healthcare Knowledge Infostructure (IHK)